Large Carnivores and the Convention on Migratory Species (CMS)—Definitions, Sustainable Use, Added Value, and Other Emerging Issues - Lewis, Melissa; Trouwborst, Arie (Frontiers in Ecology and Evolution, 2019)
The relevance of the Convention on Migratory Species (CMS) for large carnivores is on the increase. Its appendices currently feature polar bear, Gobi bear, African wild dog, lion, leopard, snow leopard and cheetah. This increased involvement raises various issues and debates concerning, inter alia, the value added by the CMS as compared to other treaties; the scope of the CMS in relation to its definition of ‘migratory species’; and the Convention’s implications for the sustainable use of listed large carnivores. We present these and similar emerging questions within their broader context, provide beginnings of answers, and outline an agenda for further research. We further highlight the need for improved interpretive guidance on aspects of the Convention’s legal text and its implications for sustainable use.